Burnout and its relationship with depressive symptoms in primary school teachers under the “Double Reduction” policy in China - Zhong, Yunhui; Lai, Shuixiu; Li, Yibo; Yang, Kan; Tang, Hong; Zhang, Xiang-yang (Frontiers in Public Health, 2025)
BackgroundThe “Double Reduction” policy requires schools to reduce Chinese students’ extracurricular activities and homework to lessen academic stress and improve mental well-being. However, there is limited research on primary school teachers’ psychological well-being within the context of the “Double Reduction” policy. This study examined self-reported burnout levels of primary school teachers and investigated the relationship between burnout and depressive symptoms in the context of the “Double Reduction” policy in China.MethodsA cross-sectional survey recruited 3,199 primary school teachers from 15 cities across China. The teachers’ burnout levels were assessed with the Maslach Burnout Inventory, and depressive symptoms were evaluated with the Patient Health Questionnaire depression scale.ResultsUnder the “Double Reduction” policy in China, 66.6% of the primary school teachers experience burnout. Individual and work-related characteristics were independently correlated with burnout. These factors included holding a bachelor’s degree (OR = 2.244, 95% CI: 1.559–3.230, p < 0.001), being married (OR = 0.598, 95% CI: 0.443–0.807, p < 0.001), being dissatisfied with one’s income (OR = 2.602, 95% CI: 2.191–3.090, p < 0.001), and having an intermediate professional title (OR = 1.351, 95% CI: 1.086–1.681, p = 0.007). The correlation coefficients between burnout subscale scores and depressive symptoms were 0.588 for emotional exhaustion, 0.585 for cynicism, and − 0.180 for professional efficacy (all p < 0.001).ConclusionOur findings indicate that the prevalence of burnout among primary school teachers in China is exceptionally high, particularly under the “Double Reduction” policy. This situation is correlated with various psychological disorders, including depression. It is crucial to urgently implement psychological interventions for primary school teachers. Specifically, psychological assistance should be targeted at educators who are bachelor degree holders, married, dissatisfied with their income, and holders of an intermediate professional title.